Computer approach using MathCAD for better understanding to the Structural Analysis II (KJC 424) / Wan Muhamad Fahmi Wan Zaki - Wan Zaki, Wan Muhamad Fahmi (2006)
This proposal describes a study that was conducted to develop a programme for the Structural Analysis II (KJC 424) using MathCAD and to encourage the KJC 424 students for better understanding in structural analysis especially indeterminate structural. This study is beneficiary to all individuals who are interested on structural analysis especially for students. Hence, it is encourage students to understand the concept of analysis. Type of structure was analyse is beam. This study focused on analyzing an indeterminate structure and Flexibility Method. The analysis of the beam (indeterminate system) in this programme consist two types of Degree of indeterminacy; it is statically indeterminate to degree 1 and 2. Methodology that involved in this study is manual calculation, method and Procedure, Modeling using MathCAD and run analysis. Manual Calculation is covered a beam the loading such as Uniform Distributed Load and point load. Method used in solving indeterminate structure is Flexibility Method (Unit Load Method). The second phase is a Method and Procedure. After manual calculation stage done, the modeling stage has began using MathCAD. The conclusion and recommendation based on the study, all the results from the programme and other software is almost similar, all the diagrams shown by the progamme is same with Stab2D software, It is concluded that we focus in our main objective which is fully related to the programme itself and to develop a better programme which is can solve a various types of structure using MathCAD’s.